Streptomyces rimosus-rich soil exposure alleviates depression-like behaviors by modulating neuroinflammation and synaptic plasticity in mice with stress - Jin Hee Kim; Jin Se Kim; Hyeyoon Eo; Sowon Yang; Choong Hwan Lee; Sin-Ae Park; Myung Sook Oh (Scientific Reports)
Abstract Soil contains a wide range of microbial communities. Recently, direct exposure to soil and soil microbes has been reported to have a positive effect on emotional integrity. Among the soil microbes, Streptomyces rimosus is known to produce geosmin, which have a unique odor and positive effects on mental status. In this context, this study aimed to investigate the effects of direct exposure to soil containing S. rimosus on depression-like behavior and depression-related factors in the mouse. To induce depression, the mice were exposed to chronic restraint stress (CRS) for 14 days, and direct soil exposure continued for 17 days from the first day of CRS. The results showed that direct exposure to soil containing S. rimosus alleviated the CRS-induced depression-like behavior. Additionally, S. rimosus-rich soil exposure reduced the activation of microglia and astrocyte in the depression-related brain area, and reduced the mRNA expression levels of cytokines including interleukin (IL)-6, interferon-γ, and IL-17 A. Moreover, S. rimosus-rich soil contact increased synaptic plasticity, which was reduced by CRS. The same effects were not observed in the group exposed to sterilized soil. Collectively, the current study suggests that S. rimosus soil contact can be a beneficial psychological therapeutic strategy for patients with mental illnesses.